Penggunaan Metode Qiroah Untuk Meningkatkan Bacaan Al-Qur’an Anak-Anak Di Rumah Tahfizh Tazkia Medan - Nur, Lutfiyah; Yuris, Evicenna (EL-EMIR INSTITUTE, 2025)
Qur’an memorization education for children is becoming increasingly important in the digital era, where the ability to read the Qur’an with tartil (proper recitation) is often neglected. At Rumah Tahfizh Tazkia Medan, the Qiroah method—emphasizing gradual repetition of recitation, correction of tajwid (rules of recitation), and strengthening of memorization—is applied to optimize the Qur’an reading skills of young children. This study aims to explore how this method can improve their reading speed, fluency, and comprehension while maintaining a high level of learning motivation. Through observation of 50 participating children, the Qiroah method involved daily sessions in small groups, where teachers guided and corrected each letter being read. The results show that 70% of the children were able to read short surahs according to tajwid principles, and learning motivation increased by 50% based on a parent survey. Challenges such as children’s fatigue were addressed through Arabic writing activities. Overall, the Qiroah method proved effective as a simple and enjoyable tool for building a strong foundation in Qur’an reading within the tahfizh environment. This recommendation can be applied in similar institutions to support a younger generation that is closer to Islamic teachings while adapting to children’s needs.